Nickel ferrite nanoparticles-hydrogen peroxide: a green catalyst-oxidant combination in chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides - Kulkarni, Aparna M.; Desai, Uday V.; Pandit, Kapil S.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Nickel ferrite nanoparticles-hydrogen peroxide has been demonstrated for the first time as a green and efficient catalyst-oxidant combination in the chemoselective oxidation of thiols to disulfides and sulfides to sulfoxides. This magnetically separable catalyst was found to be reusable for five consecutive runs without appreciable change in the activity, as well as composition of the catalyst. The mechanism for the oxidation of thiols and sulfides has also been proposed.